Powerful enterprise architecture and information technology strategies why SOA is the missing link. - Holley, Kerrie
The promises of services-oriented architecture, enterprise architecture (EA) and information technology (IT) strategies-to change IT from inhibitor to enabler of business flexibility and align IT with business strategies-are remarkably similar. However, for many companies, their EA and IT strategies have not become the catalyst for the intelligence enterprise, the sense-and-respond organization, the agile enterprise or the adaptive enterprise.